Experimental Evaluation of Geopolymer Concrete Strength Using Sea Sand and Sea Water in Mixture - Tung Pham Thanh; Tu T. Nguyen; Trung Tuan Nguyen (Civil Engineering Journal, 2022)
This paper presents the experimental strength evaluation of geopolymer concrete and ordinary concrete using sea sand and seawater in the mixture. A series of 30 cubic samples with a 150 mm side length and 12 rectangular specimens with a dimension of 100 × 100 × 400 mm (width × thickness × length) were cast and tested in this study. Specimens were divided equally into two groups. The first group of specimens was cast using geopolymer as the main binder (GPC), while the second group of samples was made using ordinary Portland Cement (OPC). While the compression tests were performed for specimens in two groups at the ages of 3, 7, 28, 60, and 120 days, the tensile tests were only performed for specimens at 7 and 28 days. The testing results revealed that the compression strength of GPC specimens using sea sand and seawater was significantly higher than that of OPC samples using the same type of salted sand and water. Besides, the use of sea sand and seawater for replacing river sand and fresh water in the production of GPC is feasible in terms of compressive strength since GPC produces a higher compressive strength than that of conventional concrete. Doi: 10.28991/CEJ-2022-08-08-03 Full Text: PDF